2013
DOI: 10.1186/1471-2474-14-230
|View full text |Cite
|
Sign up to set email alerts
|

Frequent use of blood-saving measures in elective orthopaedic surgery: a 2012 Dutch blood management survey

Abstract: BackgroundBlood loss in hip and knee arthroplasties may necessitate allogeneic blood transfusions. Different blood-saving measures (BSMs) were introduced to reduce these transfusions. Purpose of the present study was to assess the frequency of BSM use, stratified by type and hospital setting of orthopaedic departments in the Netherlands.MethodsAn internet-based questionnaire was sent to all heads of orthopaedic departments of Dutch hospitals and private clinics (n = 99). Questions were asked on how often BSMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…However, participating physicians in the interviews stated using a restrictive transfusion protocol as mentioned in the national guideline, with triggers as low as 6.4 g/dL . These statements were in line with a previous survey among chairs of orthopedic departments in the Netherlands, where 96% of orthopedic departments reported using the national transfusion guideline or an extended version of this guideline . The risks for infections due to allogeneic transfusions like hepatitis B and C or human immunodeficiency virus were not mentioned as relevant risks of transfusion in the interviews, when explicitly asked about these risks.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, participating physicians in the interviews stated using a restrictive transfusion protocol as mentioned in the national guideline, with triggers as low as 6.4 g/dL . These statements were in line with a previous survey among chairs of orthopedic departments in the Netherlands, where 96% of orthopedic departments reported using the national transfusion guideline or an extended version of this guideline . The risks for infections due to allogeneic transfusions like hepatitis B and C or human immunodeficiency virus were not mentioned as relevant risks of transfusion in the interviews, when explicitly asked about these risks.…”
Section: Discussionsupporting
confidence: 79%
“…A previous survey on the frequency of BSM use showed that more than 85% of Dutch hospitals frequently use either EPO, perioperative blood salvage, or a combination of these non–cost‐effective BSMs in THA and TKA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood salvage includes two modalities: first; intraoperative cell salvage, which is used during surgery in which a patients' blood is collected, washed, concentrated and then re‐infused, and second, a device that postoperatively collects, filters and re‐infuses autologous wound blood by means of a wound drainage and re‐infusion system (So‐Osman et al, ). Nowadays, the postoperative wound drainage system is used more commonly in primary arthroplasties opposed to intraoperative cell salvage, which is retained for more complex surgery such as revision arthroplasties (Voorn et al, ; Struijk‐Mulder et al, ; Sikorski et al, ). In a recent multicentre RCT, it was concluded that blood salvage was not effective to prevent exposure to allogeneic transfusion or to reduce the number of allogeneic red blood cell units transfused in primary elective THA and TKA and therefore could be considered low‐value care (So‐Osman et al, ,b).…”
Section: The Lisboa Studymentioning
confidence: 99%
“…The problem analysis of the LISBOA study consisted of two parts. Current use was assessed with a survey sent to all the heads of Dutch orthopaedic departments (Voorn et al, ). The survey demonstrated that 68% of the responders used ESAs on a regularly basis, intra‐operative cell salvage was used by 31% of responders, and postoperative drainage and re‐infusion was frequently used by 69% of the responders (response rate of the survey: 82%).…”
Section: The Lisboa Studymentioning
confidence: 99%